(untitled) (Journal of the College of Basic Education, 2024)
Climate studies are gaining importance in the field of applied climate, agricultural development and water resources in areas with arid and semi-arid climates, and the study area is part of it. wind) in the difference in the values of water intake (evaporation / transpiration) for the potato crop (spring and autumn), as the total values of evaporation / transpiration during the growing season for spring potatoes (547.6) mm. larger to meet growth requirements. As for the autumn potato crop, the total values of evaporation / transpiration during the growing season were (343.7) mm. Thus, the values of the water meter quantity differed. In the month of August, it was the least month, while the month of October needed a larger amount. The growth period of the potato crop.